Studies on β⇌α transition in Sn and Sn-rich alloys for a cryogenic tin bolometer. (10th April 2019) - Mazumdar, A; Garai, A; Krishnamoorthy, H; Gupta, G; Reza, A; Thamizhavel, A; Nanal, V; Pillay, R G; Shrivastava, A
Abstract: Tin pest is a concern for applications involving tin at low temperatures. Efforts have been initiated for a neutrinoless double beta decay experiment in 124 Sn— TIN.TIN (The INdia-based TIN detector). The experiment proposes to use cryogenic Sn bolometers. It is envisaged that the detector will be of large size (0.1–1 ton) and is expected to run for several years. Thus, methods of suppressing tin pest need to be investigated. In this paper, the stability of various Sn-rich alloys against tin pest and consequences for TIN.TIN have been studied. Additionally, an inconsistency in the literature data about the α → β transition temperature in Sn has been resolved using Differential Scanning Calorimetry (DSC). The α → β transition was also studied in the Sn–Cu alloy and its transition temperature was found to be 36.3 °C.